Elevated peak systolic blood pressure in endurance-trained athletes: Physiology or pathology? - Richard, N. A.; Hodges, L.; Koehle, M. S. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Blood pressure is a function of cardiac output and peripheral vascular resistance. During graded exercise testing (GXT), systolic blood pressure (SBP) is expected to increase gradually along with work rate, oxygen consumption, heart rate, and cardiac output. Individuals exposed to chronic endurance training attain a greater exercise SBP than in their untrained state and sedentary counterparts, but it is currently unknown what is considered a safe upper limit. This review discusses key studies examining blood pressure response in sedentary individuals and athletes. We highlight the physiological characteristics of highly fit individuals in terms of cardiovascular physiology and exercise blood pressure and review the state of the current literature regarding the safety of high SBP during exercise in this particular subgroup. Findings from this review indicate that a consensus on what is a normal SBP response to exercise in highly fit subjects and direct causation linking high GXT SBP to pathology is lacking. Consequently, applying GXT SBP guidelines developed for a "normal" population to endurance-trained individuals appears unsupported at this time. Lack of evidence for poor outcomes leads us to infer that elevated peak SBP in this subgroup could more likely reflect an adaptive response to training, rather than a pathological outcome. Future studies should track clinical outcomes of those achieving elevated SBP and develop athlete-specific guidelines.